Taxonomy and distribution of recent species of the subfamily Nodosariinae (Foraminifera) in Icelandic waters - Guðmundsson, Guðmundur; Cedhagen, Tomas; Andersen, Tom (European Journal of Taxonomy, 2022)
Taxonomy of fourteen very little known species of Nodosariinae Ehrenberg, 1838 in Icelandic waters is revised. Knowledge of these species in the North Atlantic relies mainly on studies in the late 19th and early 20th centuries, using large volume samplers. Later studies have emphasized quantitative samples of a few cm3 where the Nodosariinae are very rare. This study analysed 879 dredging samples where Nodosariinae occurred in 492 samples, comprising 7598 specimens of about 415 000 of all picked foraminifera. Ordination analysis of species distributions reflects prominent temperature and salinity differences that exist in the sampling area (753 000 km2) north and south of the Greenland-Scotland Ridge (GSR). Eight species are restricted to southern temperate waters (> 2°C): Dentalina mutabilis (Costa, 1855), Dentalina antarctica Parr, 1950, Dentalina antennula d’Orbigny, 1846, Dentalina filiformis (d’Orbigny, 1826), Grigelis pyrula (d’Orbigny, 1826), Grigelis guttifera (d’Orbigny, 1846) comb. nov., Grigelis semirugosus ? (d’Orbigny, 1846) and Nodosaria subsoluta Cushman, 1923. Four species (Nodosaria haliensis Eiland & Guðmundsson, 2004, Nodosaria incerta Neugeboren, 1856, Dentalina elegans d’Orbigny, 1846 and Dentalina frobisherensis Loeblich & Tappan, 1953) occur mainly north of Iceland. Two species, Dentalina obliqua (Linnaeus, 1758) and Pseudonodosaria subannulata (Cushman, 1923), have wide tolerance ranges for physical variables.